Pendidikan Kesehatan Protokol Pencegahan Covid Dan Pemeriksaan Kualitas Hidup Kepada Lansia Di GBI Bukit Pengharapan Kediri - Dewi Ika Sari Hari Poernomo; Sandy Kurniajati (Pelita Medika, 2022)
Background: During the COVID-19 Pandemic, the elderly are very vulnerable to being exposed to the COVID-19 virus because their immune system has decreased. In addition, most of the elderly have degenerative diseases, such as respiratory disease, heart disease, diabetes mellitus, hypertension, and this covid pandemic condition. can affect the quality of life of the elderly. Partners in Community Health Service are GBI Bukit Pengharapan Kediri. The problem found by the service staff is that there is still a lack of awareness in implementing the Covid-19 prevention protocol, the elderly have a high risk of being infected with the coronavirus and the Covid-19 pandemic condition can have an unfavorable impact on the quality of life of the elderly. The purpose of the Community Service activity is to increase the knowledge of the elderly in the Covid-19 prevention protocol, develop healthy behavior for the elderly in preventing Covid-19, and know the description of the quality of life of the elderly.Method: The method used is to check the vital signs of the elderly, to check the level of knowledge about Covid-19, and to check the quality of life through a Questionnaire for Service Providers providing Health Education on Covid-19 prevention protocols using videos and leaflets Result: The results of Community Service are that the elderly are enthusiastic to take part in Community Service activities, when they are given Health Education regarding the prevention of the Covid-19 Protocol and improving the quality of life of the elderly, they are actively involved in discussions. Knowledge of the elderly about the Covid-19 prevention protocol with a good category increased to 86.7% and the elderly with a good quality of life increased to 73.7% Conclusion: After receiving Health Education, the elderly experienced increased knowledge about the Covid-19 prevention protocol and improved quality of life Kata kunci: Pendidikan Kesehatan, Protokol Pencegahan Covid-19, Kualitas Hidup Lansia